Fighting Fire with Fire? Inequality, Populism and Voter Turnout - Hanna Schwander; Dominic Gohla; Armin Schäfer (Politische Vierteljahresschrift, 2020)
In this article, we ask whether the presence of populist parties influences the negative effect of income inequality on voter turnout. A~number of studies have shown that voter turnout is lower in unequal countries. In particular, citizens with fewer resources abstain at higher rates. Since populist parties seek to mobilize these groups, their success could lead to higher and less unequal turnout rates. To assess empirically whether this holds true, we analyzed a~dataset encompassing data on 296 national parliamentary elections in 31~European countries between 1970 and 2016. The results show that there is neither a~direct nor an indirect effect of populism on voter turnout. In elections with more successful populist parties, voter turnout was not significantly higher than in other elections. Higher vote shares of populist parties also do not mitigate the negative impact of income inequality on voter turnout. Finally, there does not seem to be a~difference between elections with high left-wing or right-wing populist parties' success. Neither variant of populism alters the relationship between inequality and turnout.
Keywords: 320; Voter turnout; Populism; Inequality; Participation; Political sociology; Wahlbeteiligung; Populismus; Ungleichheit; Participation; Politische Soziologie